Structural discrimination against people with mental illness; a scoping review. - Katrine Gren Voldby; Lone Christina Hellström; Marie Eva Berg; Lene Falgaard Eplov (Elsevier, 2022)
Structural discrimination against people with mental illness can be witnessed all over the world. It exists in a variety of settings including healthcare, employment, and media. For several years scholars have been aware of the problem but research on mental health-related discrimination is still finding its foothold. This paper aims to elucidate the scope of the literature regarding structural discrimination against people with a mental illness. We utilized the scoping review methodology and searched 4 databases. Our scoping review included 124 studies, mostly from high-income countries. The literature indicates that people with a mental health diagnosis are exposed to structural discrimination in several areas of life. The majority of all studies were descriptive, but twelve studies had an intervention design. In general, conceptualization, design, strategy, and content were highly heterogeneous, except for in the subarea of media. There is a lack of scientific coverage of the complex set of cooperative factors behind structural discrimination. The lack of coherence in conceptualizing, design, and outcome measures makes up a limitation in creating an overview of the field and may explain the deficient development in the field during the last 20 years. It leaves the field in a difficult place in creating innovative ways to diminish the problem of structural discrimination; accordingly, only a few interventions have been developed.